"When I think of me as a parent": Procreative options and young adults' identity motives. Issue 2 (April 2022) - Canzi, Elena; Parise, Miriam; Rosnati, Rosa; Scabini, Eugenia; Manzi, Claudia
The current study explored whether and to what extent different procreative options (natural conception, adoption, homologous techniques, and heterologous techniques) were perceived as enriching or threatening to young adults' expectation of identity motives fulfillment. Our sample consisted of 1380 Italian young adults (62.9% women) aged between 18 and 33 years who participated in a national online survey on young adulthood. Results showed that participants expect natural conception to be more enriching to their identity, whereas they expected heterologous techniques to be more threatening to their identity compared to all other procreative options. Moreover, participants perceived adoption in the event of one's partner's sterility to be more enriching to their identity compared to both homologous and heterologous assisted reproductive techniques. Data were also analyzed taking into account the participants' sex, age, and religious beliefs.